SPECIFIC FEATURES OF SOCIAL INFRASTRUCTURE OF RURAL AREA IN DONETSK REGION - Niemets, Lyudmyla; Segida, Kateryna; Yakovleva, Yuliia (Human Geography Journal, 2015)
The article is devoted to reveal the specific features of social infrastructure of rural areas in Donetsk region. Urgency of the object-subject field of research is given. The features by different part of social infrastructure (educational, cultural, medical, sanitary and resort, housing and communal, trade, transport and communication infrastructures) are analyzed by time and territorial aspects. The basic directions of optimization of social infrastructure in rural areas of Donetsk region are given.